More Choice, Less Uncertainty: The Paradoxical Relationship of Political Identity and News Exposure in the American Public Sphere - Gross, Benjamin (Cross currents, 2017)
The article explores how ambiguity is defined as a situation of inexactness, and is synonymous with the feelings of uncertainty and ambivalence. Topics discussed include uncertainty with regard to a particular event, that one can assign it some subjective probability based on believe; theory of cognitive dissonance, the internal discord felt from holding conflicting beliefs simultaneously; and challenge for humans is to form and maintain a set of beliefs.